Prevalence of Bacillus cereus s.l. in ultra-high temperature chocolate milk from selected milk manufacturers in Malaysia - Anyi, Ubong; New, Chia Yeung; Chai, Lay Ching; Loo, Yuet Ying; Mahmud @ Ab Rashid, Nor Khaizura; Kayali, Ahmad Yaman; Radu, Son (Rynnye Lyan Resources, 2020)
Bacillus cereus is a major foodborne pathogen of great concern to the dairy industry owing to its resilient spores as well as the adverse effect of its toxins. At present, there is no informational study available to solve or pinpoint the UHT chocolate milk contamination issue in Malaysia. This work aimed to investigate the prevalence and contamination level of B. cereus s.l. in UHT chocolate milk and to suggest the appropriate solution for the issue. In the present study, B. cereus s.l. prevalence and contamination level in individually packed UHT chocolate milk from processing factories was evaluated. The prevalence and concentration of B. cereus s.l. were determined via MPN-PCR (Most Probable Number-Polymerase Chain Reaction) assay. Results showed that 31.11% from 220 of UHT chocolate milk tested contained Bacillus spp.; of this Bacillus spp. positive samples, 24.30% were also positive for B. cereus s.l. with concentration ranging from less than 3 to more than 1100 MPN/mL. Findings from this study highlighted the possibility of UHT chocolate milk as a potential source of B. cereus s.l. infection. Therefore, findings emphasized the needs to revise, monitor and improve UHT sterilization process to reduce infection risk. Furthermore, it is also essential to maintain the hygiene to minimize initial microbial load and contamination of UHT chocolate milk, beginning from production to retail. © 2020 The Authors. Published by Rynnye Lyan Resources.